Pelatihan Pembuatan Desinfektan dan Hand Sanitizer Non-Alkohol di Kelurahan Seberang Padang, Kota Padang - Yulizar Yusuf; Hermansyah Aziz; Syukri Syukri; Novesar Jamarun; Bustanul Arifin; Olly Norita Tetra; Norman Ferdinal; Matlal Fajri Alif; Adlis Santoni (Warta Pengabdian Andalas, 2020)
Seberang Padang Village, South Padang District, is next to Padang City, which has approximately 200 families. This location is a crossing area between Padang-Painan, in West Sumatra. The community consists of two existing traditional markets that sell daily necessities. Besides that, there is also one elementary school, two junior high schools, and one high school. The global Covid-19 pandemic certainly affects the community's daily activities and learning activities, including children, elementary school students, middle and high school students, and the village community to fulfil their basic needs. Furthermore, the main problem of Covid-19 is not only about the effects caused by the virus on sufferers but also about its high-speed transmission. Therefore, to educate the community around the Seberang Padang village, several Chemistry Lecturers and students at the Faculty of Mathematics and Natural Sciences at Andalas University did a community engagement. They taught the community about making disinfectants and hand sanitizers without alcohol that can overcome the occurrence of Covid-19 transmission. In addition, face masks were provided for the community, and the alms of food for underprivileged residents to push down the negative impact of Covid-19.